(untitled) (Italian Review of Legal History, 2020)
The Twenties of the past century is a period of strong debate on the part of Benedetto Croce either with the politics of fascism (from which he gradually took the distance up to an open disapproval and to the undersigning of the anti-fascist intellectuals Declaration), or with legal science and with its demand to offer an autonomous perspective of knowledge. This second field of intervention is particularly characterized by the controversy with the doctrine of natural law of the philosopher Giorgio Del Vecchio and with the one of the Romanist Pietro Bonfante. In this second one particularly, the vision of the Law under Benedetto Croce point of view, i.e. the objection to the same autonomy of the legal speech, raised up in all its intensity. The distance from the politics of fascism and from the attacks brought to the legal science allowed Benedetto Croce to develop a deep and significant thought on some very general and basic topics, as the one on the origin of freedom, in the contrast between its individual and institutional dimension. Different effects we can find in the comparison between the historicism of Benedetto Croce and the tendencies of the jurists of the third decade of the twentieth century. A first, not secondary (and presumably unwilled) result of the position assumed by Croce toward the legal science was paradoxically to encourage the assumption, within the second, of a neo idealism interpretation of the law. In the attempt to affirm the supremacy of neo idealism philosophy, a sort of incorporation of the latter in the method used by the jurists in the formulation of their science took place. A second field where such comparison took place was for sure the issue about the qualification of the Law, a dogmatic ground where the progressive evolution of the relationship between individual and social moment of the Italian legal experience, in the direction of the definition in a totalitarian way of the behavior rules designed for founding the parameters of the activity of individuals, took place.